Investigating the Factors Influencing Digital Movie Piracy. (2nd September 2016) - Phau, Ian; Teah, Min; Liang, Johan
ABSTRACT: This article closes a theoretical gap in the literature by incorporating neutralization theory, mere exposure effect, self-control theory, and the theory of planned behavior to investigate social and personal factors influencing the downloading of pirated digital movies. Research was conducted using convenience sampling in a large university in Western Australia. Data were analyzed using regression models. Habitual conduct, affect, and facilitating conditions have significant influence upon attitudes toward downloading pirated movies; conversely, self-efficacy, moral judgement, and social factors do not. In addition, attitudes toward downloading pirated movies have a significant influence upon the intention to download pirated movies. It was also found that internet usage, internet time spent and internet speed do not moderate the relationship between attitudes and intention to download pirated movies. Managers, marketers and policymakers must collaborate aggressively to combat movie piracy. Marketers and policymakers can start by creating awareness campaigns to invoke the guilt factor and provide another, cheaper alternative on the internet. In addition, the punishment should be harsher and anti-piracy agencies should be more aggressive in catching all illegal downloaders by tracking their IP addresses from the internet provider that they used.